ANALISIS PENGARUH INFLASI, PENANAMAN MODAL ASING (PMA) DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI JAWA TIMUR (JEB17 : Jurnal Ekonomi dan Bisnis, 2017)
Economic growth is one of the indicators used as a benchmark, the success of development of an area of economic growth in East Java has increased and decreased. This study aims to analyze the factors affecting economic growth in East Java variables used include inflation, Foreign Investment (PMA) and labor. This study uses secondary data obtained from the Central Bureau of Statistics (BPS) of East Java, secondary data used in this study in the form of time series data from 2010-2014 period of this study using multiple linear regression analysis method with the help of spss 21 program. Based on the result of multiple linear regression analysis, the conclusion is as follows: the inflation variable has a negative and significant effect on the economic growth in East Java due to the smaller significance and the level of significance (a = 0.05) of 0.047. Foreign Investment and manpower have no significant effect on economic growth in East Java because the result is significantly greater than the level of signi ficance (a = 0.05). As for R2 in yield of 0.99 or 99%, this means that economic growth in East Java can be explained by the three independent variables of 99% and 1% explained by other factors outside the model of this study.Â Â Keywords: East Java economic growth, inflation, foreign investment (PMA) and labor.